2015
DOI: 10.2298/mpns1508245s
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behavior of street children

Abstract: Despite a small and unrepresentative sample, the results of this study indicate serious problems and significant risks associated with sexual behavior of children and young people who live and work in streets. This pilot study suggests that it is necessary to conduct new research on sexual behavior of street children and youth on a representative sample and with appropriate methodology. The results of a new study should be used to plan and carry out appropriate preventive measures regarding sexual behavior of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
(7 reference statements)
2
3
0
4
Order By: Relevance
“…9 A Serbian study revealed that among the sexually active street children, a majority had multiple partners, 41.2% had had their first sexual intercourse by the age of twelve years and only a small number of respondents used a condom. 10 A Kolkata-based study has revealed sero-positivity rates of 1% and 4% for HIV and sexually transmitted infections, respectively, with 9% of 554 respondents reporting sexual abuse. 11 A study from Vancouver found that childhood maltreatment is associated with subsequent risk of suicidal behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…9 A Serbian study revealed that among the sexually active street children, a majority had multiple partners, 41.2% had had their first sexual intercourse by the age of twelve years and only a small number of respondents used a condom. 10 A Kolkata-based study has revealed sero-positivity rates of 1% and 4% for HIV and sexually transmitted infections, respectively, with 9% of 554 respondents reporting sexual abuse. 11 A study from Vancouver found that childhood maltreatment is associated with subsequent risk of suicidal behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Dari berbagai penelitian terdahulu, dilaporkan bahwa anak jalanan sangat rentan terhadap pelecehan seksual (Hai, 2014), perilaku seksual pra-nikah (Dwijayanti & Herdiana, 2011;Stojadinović, Batrnek Antonić, Perinović & Rončević, 2015), dan penggunaan narkoba (Hai, 2014;Bah, 2018). Hal ini juga berarti bahwa anak jalanan rentan terpapar oleh infeksi menular seksual (IMS) dan HIV (Setiawan, 2007).…”
Section: Pendahuluanunclassified
“…has become her or his habitual abode and/or sources of livelihood, and who is inadequately protected, supervised or directed by responsible adults” [ 1 ]. Street children are exposed to many health problems [ 2 ] due to their poor living conditions and are at risk of developing serious communicable illnesses such as the human immunodeficiency virus (HIV(, viral hepatitis such as hepatitis B virus (HBV) and hepatitis C virus (HCV), sexually transmitted diseases (STDs) and other infections [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%